2020
DOI: 10.3390/atmos11070703
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution of Major Aerosol Types over China Based on MODIS Products between 2008 and 2017

Abstract: Knowledge of aerosol-type distribution is critical to the evaluation of aerosol–climate effects. However, research on aerosol-type distribution covering all is limited. This study characterized the spatiotemporal distribution of major aerosol types over China by using MODerate resolution Imaging Spectroradiometer (MODIS) products from 2008 to 2017. Two aerosol-type classification methods were combined to achieve this goal. One was for relatively high aerosol load (AOD ≥ 0.2) using aerosol optical depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…AOD and AE) using 13 years of data during 2001–2013 (Habib et al, 2019 ) were observed using the Aerosol Robotic Network (AERONET), Moderate Resolution Imaging Spectroradiometer (MODIS), and Multi-angle Imaging Spectroradiometer (MISR) over regions of the Asian desert. Further, according to Chen et al ( 2020 ), the background aerosols (mainly continent aerosol) dominate with a combined occurrence ratio of over 70% and they have slight variations on the seasonal scale with the dominant aerosols showing strong seasonal variations. Nonetheless, with the significance of the climatic effect of aerosols and the importance of aerosols in cloud formation, many investigations have been performed by using the data of aerosol parameters (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…AOD and AE) using 13 years of data during 2001–2013 (Habib et al, 2019 ) were observed using the Aerosol Robotic Network (AERONET), Moderate Resolution Imaging Spectroradiometer (MODIS), and Multi-angle Imaging Spectroradiometer (MISR) over regions of the Asian desert. Further, according to Chen et al ( 2020 ), the background aerosols (mainly continent aerosol) dominate with a combined occurrence ratio of over 70% and they have slight variations on the seasonal scale with the dominant aerosols showing strong seasonal variations. Nonetheless, with the significance of the climatic effect of aerosols and the importance of aerosols in cloud formation, many investigations have been performed by using the data of aerosol parameters (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…Many satellite instruments, such as the Moderate Resolution Imaging Spectroradiometer (MODIS) [5], [12][13][14], the multi-angle imaging spectroradiometer (MISR) [16], [17], the Medium Resolution Spectrum Imager (MERSI), and the Advanced Himawari Imager (AHI), have set bands to retrieve AOD. The objective of this study is to evaluate the spatiotemporal distribution and seasonal variability of aerosol optical depth (AOD) at 550 nm in the atmosphere over the Kabul city of Afghanistan based on long-term data (2001-2021) from MODIS Aqua/Terra satellite observations with 1 km×1 km resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many previous studies have analyzed aerosol optical properties using long-term data or case studies of specific regions (e.g., Kim et al, 2007;Lee et al, 2007;Shin et al, 2019;Tian et al, 2020). However, fewer studies have examined long-term variations in aerosol type (e.g., Chen et al, 2020;Ou et al, 2017). Several studies have focused on aerosol emissions (e.g., Ou et al, 2017;Song et al, 2008) and aerosol characteristics in East Asia (e.g., Li et al, 2015), because aerosol types considerably vary in this region due to the diverse range of emission sources (Kang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, it was difficult to determine whether these long-term results have had a steady effect on aerosol properties. Therefore, past studies have provided extensive aerosol data, but there have been few studies of long-term variation in aerosol types according to their optical properties (e.g., Chen et al, 2020;Ou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%